Inspired by nature: Bioinspired and biomimetic photocatalysts for biomedical applications - Ashkan Bigham; Atefeh Zarepour; Moein Safarkhani; YunSuk Huh; Arezoo Khosravi; Navid Rabiee; Siavash Iravani; Ali Zarrabi (Nano Materials Science)
The field of photocatalysis has witnessed a significant advancement in the development of bioinspired and biomimetic photocatalysts for various biomedical applications, including drug delivery, tissue engineering, cancer therapy, and bioimaging. Nature has evolved efficient light-harvesting systems and energy conversion mechanisms, which serve as a benchmark for researchers. However, reproducing such complexity and harnessing it for biomedical applications is a daunting task. It requires a comprehensive understanding of the underlying biological processes and the ability to replicate them synthetically. By utilizing light energy, these photocatalysts can trigger specific chemical reactions, leading to targeted drug release, enhanced tissue regeneration, and precise imaging of biological structures. In this context, addressing the stability, long-term performance, scalability, and cost-effectiveness of these materials is crucial for their widespread implementation in biomedical applications. While challenges such as complexity and stability persist, their advantages such as targeted drug delivery and personalized medicine make them a fascinating area of research. The purpose of this review is to provide a comprehensive analysis and evaluation of existing research, highlighting the advancements, current challenges, advantages, limitations, and future prospects of bioinspired and biomimetic photocatalysts in biomedicine.